Hydro-morphodynamic assessment processes channel forming rivers in the upper part of the Tisza River Basin (in Ukraine) - Obodovskyi, Iurii; Obodovskіy Oleksandr; Onischuk, Vasily (Journal of Education, Health and Sport, 2016)
Based on materials of field studies conducted hydro-morphodynamic assessment processes channel forming rivers in the upper part of the Tisza River Basin (in Ukraine). For the state of dynamic equilibrium system "flow-channel" the basic hydrometric and hydrodynamic characteristics. Using factor analysis, factors fluvial processes established three main groups of factors fluvial processes, making it possible to carry out a comprehensive assessment of the criteria for dynamic equilibrium hydrodynamic system "flow-channel."